Educational Language Policies in Nigeria and Zimbabwe: The Impact of EMI and Indigenous Languages on Educational Inclusion - Oris Tom-Lawyer; Michael Thomas (European Scientific Journal, ESJ, 2026)
Educational language policies in African countries are controversial because their colonial legacies continue to undervalue indigenous African languages (Sibomana, 2015). These policies, such as the Education Act (1987) in Zimbabwe, influence the future of African children as they do not always support linguistic inclusion, which in turn may impact the social, economic, and national development of a country. While this context is applicable to most African countries, few comparative studies have been undertaken to explore this subject in greater depth. To address this gap, this study examined the need for educational inclusion in the language policies of Nigeria and Zimbabwe, two of the continent’s largest economies, as both have a two-language system (Anukaenyi, 2019). The study was based on the premise that detrimental medium of instruction policies at the national level can damage learning access and inclusion (Cele, 2021). The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) principles guided the critical review of 80 publications, which spanned more than two decades (2000-2024). Findings suggested that the policies have encouraged the marginalisation of indigenous languages and harmed students’ linguistic development, as their learning continues to take place in an unfamiliar language. Furthermore, the language policies have also promoted inequality as they have not been implemented in private schools. The study recommends the need for more comparative research on the importance of inclusive teaching and learning of English in Nigeria and Zimbabwe, alongside learners’ indigenous languages, to improve effective and equitable policy implementation.